PENINGKATAN KEDISIPLINAN PADA GURU DALAM PROSES BELAJAR MENGAJAR MELALUI ETOS KERJA DI SD NEGERI 115 PEKANBARU KOTA PEKANBARU - Suryati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article examines the effectiveness of fostering work ethic in increasing the discipline of teacher attendance in the classroom while teaching and learning activities. A teacher should have at least the basic competence so that she/he has the authority and ability to apply his/her duties, especially to improve a conducive learning atmosphere. Teaching and learning activities will produce an interaction process between teachers and students. Hence, it considerably needs discipline either applied by teachers or students. The making of disciplinary situations can influence the teaching and learning process so that it can also influence goal achievement. The research in this article was a School Action Research (PTS) using a research design model of Kemmis and Mc. Taggart. The research was conducted at SD Negeri 115 Pekanbaru. The subjects of the research involved 20 teachers. Two cycles showed an improvement from cycle I to cycle II with a standard achievement of 75%. Through the development of work ethic, teacher discipline could increase and improve the teaching and learning activities.